Development of Macromedia Flash 8 Based Learning Media in Mathematics Class X Nursing In Vocational School Samarinda - Dydik Kurniawan; Yeni Astuti; Tri Wahyuningsih (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2020)
Development of Macromedia Flash 8 Based Learning Media in Mathematics Subjects in Class X Nursing in Samarinda Health Vocational School 2019/2020 and testing the feasibility of Macromedia Flash 8 Based Learning Media in Mathematics Subjects in Class X Nursing Students in Vocational School Health Samarinda 2019/2020 . The research is a type of development research using the ADDIE development model. The data analysis technique used is quantitative analysis to analyze data collected from application testing such as questionnaires and qualitative descriptive analysis or data collection. Data collected by interview, observation, documentation and questionnaire. Referring to the results of the assessment it can be concluded that the development of learning media based on Macromedia Flash 8 is feasible as a learning medium.